THE INFLUENCE OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON WORK DISCIPLINE AT THE INVESTMENT AND ONE-STOP INTEGRATED SERVICE AGENCY (DPMPTSP) OF MAKASSAR CITY - A. Shantalia Chaerunnisa; M. Ikhwan Maulana Haeruddin, Agung Widhi Kurniawan, Muhammad Ichwan Musa, Rezky Amalia Hamka (ADISAM PUBLISHER, 2024)
This research aims to test and analyze the influence of leadership style and work environment on work discipline at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Makassar City. The population in this study consists of employees of the Investment and One-Stop Integrated Service Office of Makassar City, while the sample comprises 58 respondents. This research analysis uses multiple linear regression analysis with the SPSS version 23.00 statistical application for data processing. The results of this study indicate that Leadership Style has a positive and significant effect on Work Discipline, while Work Environment has a positive but insignificant effect on Work Discipline